Accuracy and performance of the lattice Boltzmann method with 64-bit, 32-bit, and customized 16-bit number formats - Lehmann, Moritz; Krause, Mathias J.; Amati, Giorgio; Sega, Marcello; Harting, Jens; Gekle, Stephan (Physical Review E, 2022)
Fluid dynamics simulations with the lattice Boltzmann method (LBM) are very memory intensive. Alongside reduction in memory footprint, significant performance benefits can be achieved by using FP32 (single) precision compared to FP64 (double) precision, especially on GPUs. Here we evaluate the possibility to use even FP16 and posit16 (half) precision for storing fluid populations, while still carrying arithmetic operations in FP32. For this, we first show that the commonly occurring number range in the LBM is a lot smaller than the FP16 number range. Based on this observation, we develop customized 16-bit formats-based on a modified IEEE-754 and on a modified posit standard-that are specifically tailored to the needs of the LBM. We then carry out an in-depth characterization of LBM accuracy for six different test systems with increasing complexity: Poiseuille flow, Taylor-Green vortices, Karman vortex streets, lid-driven cavity, a microcapsule in shear flow (utilizing the immersed-boundary method), and, finally, the impact of a raindrop (based on a volume-of-fluid approach). We find that the difference in accuracy between FP64 and FP32 is negligible in almost all cases, and that for a large number of cases even 16-bit is sufficient. Finally, we provide a detailed performance analysis of all precision levels on a large number of hardware microarchitectures and show that significant speedup is achieved with mixed FP32/16-bit.
CRIS-Team WoS Importer:2022-08-12

A general perturbative approach for bead-based microswimmers reveals rich self-propulsion phenomena - Ziegler, Sebastian; Hubert, Maxime; Vandewalle, Nicolas; Harting, Jens; Smith, Ana-Suncana (New Journal of Physics, 2019)
Studies of model microswimmers have significantly contributed to the understanding of the principles of self-propulsion we have today. However, only a small number of microswimmer types have been amenable to analytic modeling, and further development of such approaches is necessary to identify the key features of these active systems. Here we present a general perturbative calculation scheme for swimmers composed of beads interacting by harmonic potentials and via hydrodynamics, driven by an arbitrary force protocol. The approach can be used with mobility matrices of arbitrary accuracy, and we illustrate it with the Oseen and Rotne-Prager approximations. We validate our approach by using 3 bead assemblies and comparing the results with the numerically obtained full-solutions of the governing equations of motion, as well as with existing analytic models for the linear and the triangular swimmer geometry. While recovering the relation between the force and swimming velocity, our detailed analysis and the controlled level of approximation allow us to find qualitative differences already in the far field flow of the devices. Consequently, we are able to identify a behavior of the swimmer that is richer than predicted in previous models. Given its generality, the framework can be applied to any swimmer geometry, driving protocol and bead interactions, as well as in problems involving many swimmers.
CRIS-Team Scopus Importer:2019-12-10
Keywords: active matter; low Reynolds number dynamics; microswimmers; perturbation theory; self-propulsion

A phase-field model for the evaporation of thin film mixtures - Ronsin, Olivier; Jang, Dongju; Egelhaaf, Hans-Joachim; Brabec, Christoph; Harting, Jens (Physical Chemistry Chemical Physics, 2020)

Bioinspired acousto-magnetic microswarm robots with upstream motility - Ahmed, Daniel; Sukhov, Alexander; Hauri, David; Rodrigue, Dubon; Maranta, Gian; Harting, Jens; Nelson, Bradley J. (Nature Machine Intelligence, 2021)
The ability to propel against flows, that is, to perform positive rheotaxis, can provide exciting opportunities for applications in targeted therapeutics and non-invasive surgery. So far no biocompatible technologies exist for navigating microparticles upstream when they are in a background fluid flow. Inspired by many naturally occurring microswimmers-such as bacteria, spermatozoa and plankton-that utilize the no-slip boundary conditions of the wall to exhibit upstream propulsion, here we report on the design and characterization of self-assembled microswarms that can execute upstream motility in a combination of external acoustic and magnetic fields. Both acoustic and magnetic fields are safe to humans, non-invasive, can penetrate deeply into the human body and are well-developed in clinical settings. The combination of both fields can overcome the limitations encountered by single actuation methods. The design criteria of the acoustically induced reaction force of the microswarms, which is needed to perform rolling-type motion, are discussed. We show quantitative agreement between experimental data and our model that captures the rolling behaviour. The upstream capability provides a design strategy for delivering small drug molecules to hard-to-reach sites and represents a fundamental step towards the realization of micro- and nanosystem navigation against the blood flow.
CRIS-Team WoS Importer:2021-01-29

Calculation of thermodynamic properties of finite Bose-Einstein systems - Borrmann, Peter; Harting, Jens; Mülken, Oliver; Hilf, Eberhard R. (Physical Review A, 1999)

Capillary-bridge forces between solid particles: Insights from lattice Boltzmann simulations - Yang, Lei; Sega, Marcello; Harting, Jens (AIChE Journal, 2021)
Liquid capillary-bridge formation between solid particles has a critical influence on the rheological properties of granular materials and, in particular, on the efficiency of fluidized bed reactors. The available analytical and semi-analytical methods have inherent limitations, and often do not cover important aspects, like the presence of non-axisymmetric bridges. Here, we conduct numerical simulations of the capillary bridge formation between equally and unequally sized solid particles using the lattice Boltzmann method, and provide an assessment of the accuracy of different families of analytical models. We find that some of the models taken into account are shown to perform better than others. However, all of them fail to predict the capillary force for contact angles larger than pi/2, where a repulsive capillary force attempts to push the solid particle outward to minimize the surface energy, especially at a small separation distance. We then apply the most suitable model to study the impact of capillary interactions on particle clustering using a coupled lattice Boltzmann and Discrete Element method.
CRIS-Team WoS Importer:2021-07-09

Capillary interactions between soft capsules protruding through thin fluid films - Wouters, Maarten; Aouane, Othmane; Sega, Marcello; Harting, Jens (Soft Matter, 2020)
When a suspension dries, the suspending fluid evaporates, leaving behind a dry film composed of the suspended particles. During the final stages of drying, the height of the fluid film on the substrate drops below the particle size, inducing local interface deformations that lead to strong capillary interactions among the particles. Although capillary interactions between rigid particles are well studied, much is still to be understood about the behaviour of soft particles and the role of their softness during the final stages of film drying. Here, we use our recently-introduced numerical method that couples a fluid described using the lattice Boltzmann approach to a finite element description of deformable objects to investigate the drying process of a film with suspended soft particles. Our measured menisci deformations and lateral capillary forces, which agree well with previous theoretical and experimental works in case of rigid particles, show that the deformations become smaller with increasing particle softness, resulting in weaker lateral interaction forces. At large interparticle distances, the force approaches that of rigid particles. Finally, we investigate the time dependent formation of particle clusters at the late stages of the film drying.
CRIS-Team WoS Importer:2021-01-22

Catalytic flow with a coupled finite difference — Lattice Boltzmann scheme - Kulyk, Nadiia; Berger, Daniel; Smith, Ana-Suncana; Harting, Jens (Computer Physics Communications, 2020)
Many catalyst devices employ flow through porous structures, which leads to a complex macroscopic mass and heat transport. To unravel the detailed dynamics of the reactive gas flow, we present an all-encompassing model, consisting of thermal lattice Boltzmann model by Kang et al., used to solve the heat and mass transport in the gas domain, coupled to a finite differences solver for the heat equation in the solid via thermal reactive boundary conditions for a consistent treatment of the reaction enthalpy. The chemical surface reactions are incorporated in a flexible fashion through flux boundary conditions at the gas–solid interface. We scrutinize the thermal FD-LBM by benchmarking the macroscopic transport in the gas domain as well as conservation of the enthalpy across the solid–gas interface. We exemplify the applicability of our model by simulating the reactive gas flow through a microporous material catalyzing the so-called water-gas-shift reaction.
CRIS-Team Scopus Importer:2020-07-03
Keywords: Catalytic flow; Conjugated heat transfer; Reaction enthalpy; Thermal lattice Boltzmann method

Chemically Reactive Thin Films: Dynamics and Stability - Richter, Tilman; Malgaretti, Paolo; Koller, Thomas Manfred; Harting, Jens (Advanced Materials Interfaces, 2025)
Catalyst particles or complexes suspended in liquid films can trigger chemical reactions leading to inhomogeneous concentrations of reactants and products in the film. It is demonstrated that the sensitivity of the liquid film's gas–liquid surface tension to these inhomogeneous concentrations strongly impacts the film stability. Using linear stability analysis, novel scenarios are identified in which the film can be either stabilized or destabilized by the reactions. Furthermore, it is found so far unrevealed rupture mechanisms which are absent in the chemically inactive case. The linear stability predictions are confirmed by numerical simulations, which also demonstrate that the shape of chemically active droplets can depart from the spherical cap and that unsteady states such as traveling and standing waves might appear. Finally, critically discussed the relevance of the predictions by showing that the range of the selected parameters is well accessible by typical experiment

Controllable Capillary Assembly of Magnetic Ellipsoidal Janus Particles into Tunable Rings, Chains and Hexagonal Lattices - Xie, Qingguang; Harting, Jens (Advanced Materials, 2021)
Colloidal assembly at fluid interfaces has a great potential for the bottom-up fabrication of novel structured materials. However, challenges remain in realizing controllable and tunable assembly of particles into diverse structures. Herein, the capillary assembly of magnetic ellipsoidal Janus particles at a fluid–fluid interface is reported. Depending on their tilt angle, that is, the angle the particle main axis forms with the fluid interface, these particles deform the interface and generate capillary dipoles or hexapoles. Driven by capillary interactions, multiple particles thus assemble into chain-, hexagonal-lattice-, and ring-like structures, which can be actively controlled by applying an external magnetic field. A field-strength phase diagram is predicted in which various structures are present as stable states. Owing to the diversity, controllability, and tunability of assembled structures, magnetic ellipsoidal Janus particles at fluid interfaces could therefore serve as versatile building blocks for novel materials.
CRIS-Team Scopus Importer:2021-01-22
Keywords: controllable assembly; ellipsoids; Janus particles; particle-laden fluid interfaces

Curvature estimation from a volume-of-fluid indicator function for the simulation of surface tension and wetting with a free-surface lattice Boltzmann method - Bogner, Simon; Rüde, Ulrich; Harting, Jens (Physical Review E, 2016)
The free surface lattice Boltzmann method (FSLBM) is a combination of the hydrodynamic lattice Boltzmann method with a volume-of-fluid (VOF) interface capturing technique for the simulation of incompressible free surface flows. Capillary effects are modeled by extracting the curvature of the interface from the VOF indicator function and imposing a pressure jump at the free boundary. However, obtaining accurate curvature estimates from a VOF description can introduce significant errors. This article reports numerical results for three different surface tension models in standard test cases and compares the according errors in the velocity field (spurious currents). Furthermore, the FSLBM is shown to be suited to simulate wetting effects at solid boundaries. To this end, a new method is developed to represent wetting boundary conditions in a least-squares curvature reconstruction technique. The main limitations of the current FSLBM are analyzed and are found to be caused by its simplified advection scheme. Possible improvements are suggested.

Desorption energy of soft particles from a fluid interface - Mehrabian, Hadi; Snoeijer, Jacco H.; Harting, Jens (Soft Matter, 2020)
The efficiency of soft particles to stabilize emulsions is examined by measuring their desorption free energy, i.e., the mechanical work required to detach the particle from a fluid interface. Here, we consider rubber-like elastic as well as microgel particles, using coarse-grained molecular dynamics simulations. The energy of desorption is computed for two and three-dimensional configurations by means of the mean thermodynamic integration method. It is shown that the softness affects the particle-interface binding in two opposing directions as compared to rigid particles. On the one hand, a soft particle spreads at the interface and thereby removes a larger unfavorable liquid-liquid contact area compared to rigid particles. On the other hand, softness provides the particle with an additional degree of freedom to get reshaped instead of deforming the interface, resulting in a smaller restoring force during the detachment. It is shown that the first effect prevails so that a soft spherical particle attaches to the fluid interface more strongly than rigid spheres. Finally, we consider microgel particles both in the swollen and in the collapsed state. Surprisingly, we find that the latter has a larger binding energy. All results are rationalised using thermodynamic arguments and thereby offer detailed insights into the desorption energy of soft particles from fluid interfaces. This journal is
CRIS-Team Scopus Importer:2020-10-16

Early Detection of Agglomeration in Fluidized Beds by Means ofFrequency Analysis of Pressure Fluctuations - Leimbach, Steffen; Lukas, Johannes; Kolb, Sebastian; Yang, Lei; Plankenbühler, Thomas; Sega, Marcello; Harting, Jens; Karl, Jürgen (Energy & Fuels, 2022)
For description of thefluidization state offluidizedbeds, both time-domain and frequency-domain analyses of high-frequency pressurefluctuations are established approaches.Common methods for the detection of agglomeration ordefluidization influidized beds use the variance or the standarddeviation of the pressure signal or the maximum in its frequencyspectrum. These methods are used, for example, in biomasscombustion or gasification. However, these approaches lack thereliability for applications as an early agglomeration warningsystem in industrial applications. To address this issue, the presentstudy introduces a robust methodology by means of extracting acharacteristic frequency from the power spectral density of thepressure signal. A comparison of our developed approach with thecommonly used frequency maximum and standard deviation for predicting the onset of agglomeration in laboratory experimentsshows promising sensitivity on agglomeration formation. In order to evaluate the general applicability of this method on an industrialscale, this work investigates dependencies of possible influences, such as gas velocity, sand quantity, and temperature, on thecharacteristic frequency. The results indicate that the characteristic frequency can be a promising and robust method for the earlydetection of the onset of agglomeration in industrial plants.

Equilibrium Orientation and Adsorption of an Ellipsoidal Janus Particle at a Fluid-Fluid Interface - Gunther, Florian; Xie, Qingguang; Harting, Jens (Colloids and Interfaces, 2020)
We investigate the equilibrium orientation and adsorption process of a single, ellipsoidal Janus particle at a fluid-fluid interface. The particle surface comprises equally sized parts that are hydrophobic or hydrophilic. We present free energy models to predict the equilibrium orientation and compare the theoretical predictions with lattice Boltzmann simulations. We find that the deformation of the fluid interface strongly influences the equilibrium orientation of the Janus ellipsoid. The adsorption process of the Janus ellipsoid can lead to different final orientations determined by the interplay of particle aspect ratio and particle wettablity contrast.
CRIS-Team WoS Importer:2021-01-08

Formation of Crystalline Bulk Heterojunctions in Organic Solar Cells: Insights from Phase-Field Simulations - Ronsin, Olivier; Harting, Jens (ACS Applied Materials and Interfaces, 2022)
The performance of organic solar cells strongly depends on the bulk-heterojunction (BHJ) morphology of the photoactive layer. This BHJ forms during the drying of the wet-deposited solution, because of physical processes such as crystallization and/or liquid-liquid phase separation (LLPS). However, the process-structure relationship remains insufficiently understood. In this work, a recently developed, coupled phase-field-fluid mechanics framework is used to simulate the BHJ formation upon drying. For the first time, this allows to investigate the interplay between all the relevant physical processes (evaporation, crystal nucleation and growth, liquid demixing, composition-dependent kinetic properties), within a single coherent theoretical framework. Simulations for the model system P3HT-PCBM are presented. The comparison with previously reported in situ characterization of the drying structure is very convincing: The morphology formation pathways, crystallization kinetics, and final morphology are in line with experimental results. The final BHJ morphology is a subtle mixture of pure crystalline donor and acceptor phases, pure and mixed amorphous domains, which depends on the process parameters and material properties. The expected benefit of such an approach is to identify physical design rules for ink formulation and processing conditions to optimize the cell's performance. It could be applied to recent organic material systems in the future.
CRIS-Team Scopus Importer:2022-11-11
Keywords: bulk heterojunction; organic photovoltaics; phase-field simulations; process-structure relationship; thin film

Inertial focusing of a dilute suspension in pipe flow - Aouane, Othmane; Sega, Marcello; Baeuerlein, Bastian; Avila, Kerstin; Harting, Jens (Physics of Fluids, 2022)

Inertial focusing of a dilute suspension in pipe flow - Aouane, Othmane; Sega, Marcello; Baeuerlein, Bastian; Avila, Kerstin; Harting, Jens (Physics of Fluids, 2022)
The dynamics of rigid particle suspensions in a wall-bounded laminar flow present several nontrivial and intriguing features, including particle ordering, lateral transport, and the appearance of stable, preferential locations like the Segre-Silberberg annulus. The formation of more than one annulus is a particularly puzzling phenomenon that is still not fully explained. Here, we present numerical simulation results of a dilute suspension of particles in (periodic) pipe flow based on the lattice Boltzmann and the discrete element methods. Our simulations provide access to the full radial position history of the particles while traveling downstream. This allows to accurately quantify the transient and steady states. We observe the formation of the secondary, inner annulus and show that its position invariably shifts toward the Segre-Silberberg one if the channel is sufficiently long, proving that it is, in fact, a transient feature for Reynolds numbers (Re) up to 600. We quantify the variation of the channel focusing length ( L-s/2R) with Re. Interestingly and unlike the theoretical prediction for a point-like particle, we observe that L-s/2R increases with Re for both the single particle and the suspension.
CRIS-Team WoS Importer:2022-12-02

Inertial migration of oblate spheroids in a plane channel - Nizkaya, Tatiana V.; Gekova, Anna S.; Harting, Jens; Asmolov, Evgeny S.; Vinogradova, Olga I. (Physics of Fluids, 2020)
We discuss an inertial migration of oblate spheroids in a plane channel, where the steady laminar flow is generated by a pressure gradient. Our lattice Boltzmann simulations show that spheroids orient in the flow, so that their minor axis coincides with the vorticity direction (a log-rolling motion). Interestingly, for spheroids of moderate aspect ratios, the equilibrium positions relative to the channel walls depend only on their equatorial radius a. By analyzing the inertial lift force, we argue that this force is proportional to a3b, where b is the polar radius, and conclude that the dimensionless lift coefficient of the oblate spheroid does not depend on b and is equal to that of the sphere of radius a.
CRIS-Team Scopus Importer:2020-12-11

In Situ Probing the Crystallization Kinetics in Gas-Quenching-Assisted Coating of Perovskite Films - Qiu, Shudi; Majewski, Martin; Dong, Lirong; Jang, Dongju; Le Corre, Vincent Marc; García Cerrillo, José; Ronsin, Olivier J.J.; Yang, Fu; Guo, Fei; Zhang, Kaicheng; Lüer, Larry; Harting, Jens; et al. (Advanced Energy Materials, 2024)
The pursuit of commercializing perovskite photovoltaics is driving the development of various scalable perovskite crystallization techniques. Among them, gas quenching is a promising crystallization approach for high-throughput deposition of perovskite films. However, the perovskite films prepared by gas-quenching assisted blade coating are susceptible to the formation of pinholes and frequently show inferior crystallinity if the interplay between film coating, film drying, and crystallization kinetics is not fully optimized. That arguably requires a thorough understanding of how single processing steps influence the crystallization kinetics of printed perovskite films. Here, in situ optical spectroscopies are integrated into a doctor-blading setup that allows to real-time monitor film formation during the gas-quenching process. It is found that the essential role of gas quenching treatment is in achieving a smooth and compact perovskite film by controlling the nucleation rate. Moreover, with the assistance of phase-field simulations, the role of excessive methylammonium iodide is revealed to increase grain size by accelerating the crystal growth rate. These results show a tailored control of crystal growth rate is critical to achieving optimal film quality, leading to fully printed solar cells with a champion power conversion efficiency of 19.50% and mini solar modules with 15.28% efficiency are achieved.
CRIS-Team Scopus Importer:2024-01-12
Keywords: blade coating; fully printed perovskite photovoltaics; gas quenching; in situ techniques; phase-field simulations

Instability of particle inertial migration in shear flow - Asmolov, Evgeny S.; Nizkaya, Tatiana V.; Harting, Jens; Vinogradova, Olga I. (Physics of Fluids, 2021)
In a shear flow, particles migrate to their equilibrium positions in the microchannel. Here, we demonstrate theoretically that if particles are inertial, this equilibrium can become unstable due to the Saffman lift force. We derive an expression for the critical Stokes number that determines the onset of instable equilibrium. We also present results of lattice Boltzmann simulations for spherical particles and prolate spheroids to validate the analysis. Our work provides a simple explanation of several unusual phenomena observed in earlier experiments and computer simulations, but never interpreted before in terms of the unstable equilibrium.
CRIS-Team Scopus Importer:2021-10-08

Interplay of wall force field and wall physical characteristics on interfacial phenomena of a nano-confined gas medium - Rabani, Reza; Heidarinejad, Ghassem; Harting, Jens; Shirani, Ebrahim (International Journal of Thermal Sciences, 2020)
The effect of the wall force field and the wall physical characteristics on the interfacial phenomena of a 5.4 nm nanoconfined gas medium are investigated by applying three-dimensional molecular dynamics simulations. Assuming that a range of 1 nm from each wall is affected by the wall force field, the gas distribution changes notably in this region which covers 40% of the channel height. Therefore, a combined effect of the wall force field and the wall stiffness, its mass as well as the interaction strength determines the interfacial phenomena such as interfacial thermal resistance (ITR) at the gas/solid interface. The increment in interaction strength of the gas/solid atoms leads to an increase in the amount of adsorbed gas on the wall which reduces the temperature jump and ITR notably. When the ratio between the interaction strengths of the gas/solid to the gas/gas atoms exceeds 4, the temperature jump and the ITR reduce to zero. As the wall becomes stiffer, the temperature jump and consequently the ITR are increased considerably. Simultaneously, the temperature distribution in the gas medium along the channel height becomes more and more independent of the gas density as the wall stiffness increases. It is observed that as the ratio between the mass of the wall and the gas atoms increases up to 2, the temperature jump reduces notably. Meanwhile, as the wall atoms become heavier, an increment in the temperature jump is observed. Consequently, the minimum ITR occurs at a ratio of 2. It is also shown that the temperature profile in the bulk region of the channel is approximately independent of the wall mass. Considering several metals as the wall material, our analysis reveals that silver, copper, and nickel experience the least ITR among the others.
CRIS-Team Scopus Importer:2020-04-07
Keywords: Dense gas; Dilute gas; Gas adsorption; Interfacial thermal resistance; Temperature jump

Lattice Boltzmann method for thin-liquid-film hydrodynamics - Zitz, Stefan; Scagliarini, A.; Maddu, S.; Darhuber, A. A.; Harting, Jens (Physical Review E, 2019)
We propose an approach to the numerical simulation of thin-film flows based on the lattice Boltzmann method. We outline the basic features of the method, show in which limits the expected thin-film equations are recovered, and perform validation tests. The numerical scheme is applied to the viscous Rayleigh-Taylor instability of a thin film and to the spreading of a sessile drop toward its equilibrium contact angle configuration. We show that the Cox-Voinov law is satisfied and that the effect of a tunable slip length on the substrate is correctly captured. We address, then, the problem of a droplet sliding on an inclined plane, finding that the Capillary number scales linearly with the Bond number, in agreement with experimental results. At last, we demonstrate the ability of the method to handle heterogenous and complex systems by showcasing the controlled dewetting of a thin film on a chemically structured substrate.
Created from Fastlane, Scopus look-up

Lattice Boltzmann simulations of drying suspensions of soft particles - Wouters, M.; Aouane, O.; Sega, M.; Harting, Jens (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2021)
The ordering of particles in the drying process of a colloidal suspension is crucial in determining the properties of the resulting film. For example, microscopic inhomogeneities can lead to the formation of cracks and defects that can deteriorate the quality of the film considerably. This type of problem is inherently multiscale and here we study it numerically, using our recently developed method for the simulation of soft polymeric capsules in multicomponent fluids. We focus on the effect of the particle softness on the film microstructure during the drying phase and how it relates to the formation of defects. We quantify the order of the particles by measuring both the Voronoi entropy and the isotropic order parameter. Surprisingly, both observables exhibit a non-monotonic behaviour when the softness of the particles is increased. We further investigate the correlation between the interparticle interaction and the change in the microstructure during the evaporation phase. We observe that the rigid particles form chain-like structures that tend to scatter into small clusters when the particle softness is increased. This article is part of the theme issue 'Progress in mesoscale methods for fluid dynamics simulation'.
CRIS-Team WoS Importer:2021-09-17
Keywords: clusters; lattice Boltzmann simulation; capillary interactions; soft particles suspensions; thin films

Lattice Boltzmann simulations of stochastic thin film dewetting - Zitz, Stefan; Scagliarini, A.; Harting, Jens (Physical Review E, 2021)
We study numerically the effect of thermal fluctuations and of variable fluid-substrate interactions on the spontaneous dewetting of thin liquid films. To this aim, we use a recently developed lattice Boltzmann method for thin liquid film flows, equipped with a properly devised stochastic term. While it is known that thermal fluctuations yield shorter rupture times, we show that this is a general feature of hydrophilic substrates, irrespective of the contact angle θ. The ratio between deterministic and stochastic rupture times, though, decreases with θ. Finally, we discuss the case of fluctuating thin film dewetting on chemically patterned substrates and its dependence on the form of the wettability gradients.
CRIS-Team Scopus Importer:2021-09-17

Liquid film rupture beyond the thin-film equation: A multi-component lattice Boltzmann study - Pelusi, F.; Sega, M.; Harting, Jens (Physics of Fluids, 2022)
Under the condition of partial surface wettability, thin liquid films can be destabilized by small perturbations and rupture into droplets. As successfully predicted by the thin film equation (TFE), the rupture dynamics are dictated by the liquid-solid interaction. The theory describes the latter using the disjoining pressure or, equivalently, the contact angle. The introduction of a secondary fluid can lead to a richer phenomenology, thanks to the presence of different fluid/surface interaction energies but has so far not been investigated. In this work, we study the rupture of liquid films with different heights immersed in a secondary fluid using a multi-component lattice Boltzmann (LB) approach. We investigate a wide range of surface interaction energies, equilibrium contact angles, and film thicknesses. We found that the rupture time can differ by about one order of magnitude for identical equilibrium contact angles but different surface free energies. Interestingly, the TFE describes the observed breakup dynamics qualitatively well, up to equilibrium contact angles as large as 130 . A small film thickness is a much stricter requirement for the validity of the TFE, and agreement with LB results is found only for ratios epsilon = h / L of the film height h and lateral system size L, such as epsilon <= x 10(-3).
CRIS-Team WoS Importer:2022-07-01

Modelling diffusive transport of particles interacting with slit nanopore walls: The case of fullerenes in toluene filled alumina pores - Baer, Andreas; Malgaretti, Paolo; Kaspereit, Malte; Harting, Jens; Smith, Ana-Suncana (Journal of Molecular Liquids, 2022)

Monolayer Structures of Supramolecular Antagonistic Salt Aggregates - Jung, Wieland David Krischan; Harting, Jens; Sega, Marcello (Journal of Physical Chemistry B, 2021)
The speculated presence of monomolecular lamellae of antagonistic salts in oil-water mixtures has left several open questions besides their hypothetical existence, including their microscopic structure and stabilization mechanism. Here, we simulate the spontaneous formation of supramolecular aggregates of the antagonistic salt sodium tetraphenylborate (NaBPh4) in water and 3-methylpyridine (3-MP) at the atomistic level. We show that, indeed, the lamellae are formed by a monomolecular layer of the anion, enveloped by 3-MP and hydrated sodium counterions. To understand which thermodynamic forces drive the aggregation, we compare the full-atomistic model with a simplified one for the salt and show that the strong hydrophobic effect granted by the large excluded volume of the anion, together with electrostatic repulsion, suffice to explain the stability of the monomolecular lamellae.
CRIS-Team Scopus Importer:2021-04-09

Numerical simulations of self-diffusiophoretic colloids at fluid interfaces - Peter, T.; Malgaretti, P.; Rivas, N.; Scagliarini, A.; Harting, Jens; Dietrich, S. (Soft Matter, 2020)
The dynamics of active colloids is very sensitive to the presence of boundaries and interfaces which therefore can be used to control their motion. Here we analyze the dynamics of active colloids adsorbed at a fluid-fluid interface. By using a mesoscopic numerical approach which relies on an approximated numerical solution of the Navier-Stokes equation, we show that when adsorbed at a fluid interface, an active colloid experiences a net torque even in the absence of a viscosity contrast between the two adjacent fluids. In particular, we study the dependence of this torque on the contact angle of the colloid with the fluid-fluid interface and on its surface properties. We rationalize our results via an approximate approach which accounts for the appearance of a local friction coefficient. By providing insight into the dynamics of active colloids adsorbed at fluid interfaces, our results are relevant for two-dimensional self assembly and emulsion stabilization by means of active colloids.
CRIS-Team Scopus Importer:2020-04-24

Phase-Field Simulation of Liquid-Vapor Equilibrium and Evaporation of Fluid Mixtures - Ronsin, Olivier; Jang, Dong Ju; Egelhaaf, Hans-Joachim; Brabec, Christoph; Harting, Jens (ACS Applied Materials and Interfaces, 2021)
In solution processing of thin films, the material layer is deposited from a solution composed of several solutes and solvents. The final morphology and hence the properties of the film often depend on the time needed for the evaporation of the solvents. This is typically the case for organic photoactive or electronic layers. Therefore, it is important to be able to predict the evaporation kinetics of such mixtures. We propose here a new phase-field model for the simulation of evaporating fluid mixtures and simulate their evaporation kinetics. Similar to the Hertz-Knudsen theory, the local liquid-vapor (LV) equilibrium is assumed to be reached at the film surface and evaporation is driven by diffusion away from this gas layer. In the situation where the evaporation is purely driven by the LV equilibrium, the simulations match the behavior expected theoretically from the free energy: for evaporation of pure solvents, the evaporation rate is constant and proportional to the vapor pressure. For mixtures, the evaporation rate is in general strongly time-dependent because of the changing composition of the film. Nevertheless, for highly nonideal mixtures, such as poorly compatible fluids or polymer solutions, the evaporation rate becomes almost constant in the limit of low Biot numbers. The results of the simulation have been successfully compared to experiments on a polystyrene-toluene mixture. The model allows to take into account deformations of the liquid-vapor interface and, therefore, to simulate film roughness or dewetting.
CRIS-Team Scopus Importer:2021-12-24
Keywords: evaporation; film drying; liquid-vapor equilibrium; phase-field

Phoretic colloids close to and trapped at fluid interfaces - Malgaretti, Paolo; Harting, Jens (ChemNanoMat, 2021)
The active motion of phoretic colloids leads them to accumulate at boundaries and interfaces. Such an excess accumulation, with respect to their passive counterparts, makes the dynamics of phoretic colloids particularly sensitive to the presence of boundaries and pave new routes to externally control their single particle as well as collective behavior. Here we review some recent theoretical results about the dynamics of phoretic colloids close to and adsorbed at fluid interfaces in particular highlighting similarities and differences with respect to solid-fluid interfaces.
CRIS-Team Scopus Importer:2021-07-16
Keywords: active matter; fluid interfaces; microswimmers; phoretic colloids

Precision of Radiation Chemistry Networks: Playing Jenga with Kinetic Models for Liquid-Phase Electron Microscopy - Fritsch, Birk; Malgaretti, Paolo; Harting, Jens; Mayrhofer, Karl J.; Hutzler, Andreas (Precision Chemistry, 2023)
Liquid-phase transmission electron microscopy (LP-TEM) is a powerful tool to gain unique insights into dynamics at the nanoscale. The electron probe, however, can induce significant beam effects that often alter observed phenomena such as radiolysis of the aqueous phase. The magnitude of beam-induced radiolysis can be assessed by means of radiation chemistry simulations potentially enabling quantitative application of LP-TEM. Unfortunately, the computational cost of these simulations scales with the amount of reactants regarded. To minimize the computational cost, while maintaining accurate predictions, we optimize the parameter space for the solution chemistry of aqueous systems in general and for diluted HAuCl4 solutions in particular. Our results indicate that sparsened kinetic models can accurately describe steady-state formation during LP-TEM and provide a handy prerequisite for efficient multidimensional modeling. We emphasize that the demonstrated workflow can be easily generalized to any kinetic model involving multiple reaction pathways.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Electron beam effects; gold; kinetic modeling; liquid cell transmission electron microscopy; radiolysis; simulation efficiency

Probing sedimentation non-ideality of particulate systems using analytical centrifugation - Uttinger, Maximilian; Jung, Wieland David Krischan; Dao, Thi Quynh Nhi; Canziani, Herbert; Lübbert, Christian; Vogel, Nicolas; Peukert, Wolfgang; Harting, Jens; Walter, Johannes (Soft Matter, 2021)
Analytical centrifugation is a versatile technique for the quantitative characterization of colloidal systems including colloidal stability. The recent developments in data acquisition and evaluation allow the accurate determination of particle size, shape anisotropy and particle density. High precision analytical centrifugation is in particular suited for the study of particle interactions and concentration-dependent sedimentation coefficients. We present a holistic approach for the quantitative determination of sedimentation non-ideality via analytical centrifugation for polydisperse, plain and amino-functionalized silica particles spanning over one order of magnitude in particle size between 100 nm and 1200 nm. These systems typically behave as neutral hard spheres as predicted by auxiliary lattice Boltzmann simulations. The extent of electrostatic interactions and their impact on sedimentation non-ideality can be quantified by the repulsion range, which is the ratio of the Debye length and the average interparticle distance. Experimental access to the repulsion range is provided through conductivity measurements. With the experimental repulsion range at hand, we estimate the effect of polydispersity on concentration-dependent sedimentation properties through a combination of lattice Boltzmann and Brownian dynamics simulations. Finally, we determine the concentration-dependent sedimentation properties of charge-stabilized, fluorescently-labeled silica particles with a nominal particle size of 30 nm and reduced interparticle distance, hence an elevated repulsion range. Overall, our results demonstrate how the influence of hard-sphere type and electrostatic interactions can be quantified when probing sedimentation non-ideality of particulate systems using analytical centrifugation even for systems exhibiting moderate sample heterogeneity and complex interactions.<br

Pumping and Mixing in Active Pores - Antunes, G. C.; Malgaretti, P.; Harting, Jens; Dietrich, S. (Physical Review Letters, 2022)
We show both numerically and analytically that a chemically patterned active pore can act as a micro- or nanopump for fluids, even if it is fore-aft symmetric. This is possible due to a spontaneous symmetry breaking which occurs when advection rather than diffusion is the dominant mechanism of solute transport. We further demonstrate that, for pumping and tuning the flow rate, a combination of geometrical and chemical inhomogeneities is required. For certain parameter values, the flow is unsteady, and persistent oscillations with a tunable frequency appear. Finally, we find that the flow exhibits convection rolls and hence promotes mixing in the low Reynolds number regime.
CRIS-Team Scopus Importer:2022-11-25

Rolling microswarms along acoustic virtual walls - Zhang, Zhiyuan; Sukhov, Alexander; Harting, Jens; Malgaretti, Paolo; Ahmed, Daniel (Nature Communications, 2022)
Rolling is a ubiquitous transport mode utilized by living organisms and engineered systems. However, rolling at the microscale has been constrained by the requirement of a physical boundary to break the spatial homogeneity of surrounding mediums, which limits its prospects for navigation to locations with no boundaries. Here, in the absence of real boundaries, we show that microswarms can execute rolling along virtual walls in liquids, impelled by a combination of magnetic and acoustic fields. A rotational magnetic field causes individual particles to self-assemble and rotate, while the pressure nodes of an acoustic standing wave field serve as virtual walls. The acoustic radiation force pushes the microswarms towards a virtual wall and provides the reaction force needed to break their fore-aft motion symmetry and induce rolling along arbitrary trajectories. The concept of reconfigurable virtual walls overcomes the fundamental limitation of a physical boundary being required for universal rolling movements.
CRIS-Team Scopus Importer:2022-12-09

Squeezing multiple soft particles into a constriction: Transition to clogging - Bielinski, Clément; Aouane, Othmane; Harting, Jens; Kaoui, Badr (Physical Review E, 2021)
We study numerically how multiple deformable capsules squeeze into a constriction. This situation is largely encountered in microfluidic chips designed to manipulate living cells, which are soft entities. We use fully three-dimensional simulations based on the lattice Boltzmann method to compute the flow of the suspending fluid and on the immersed boundary method to achieve the two-way fluid-structure interaction. The mechanics of the capsule membrane elasticity is computed with the finite-element method. We obtain two main states: continuous passage of the particles and their blockage that leads to clogging the constriction. The transition from one state to another is dictated by the ratio between the size of the capsules and the constriction width and by the capsule membrane deformability. The latter is found to enhance particle passage through narrower constrictions, where rigid particles with similar diameter are blocked and lead to clogging.
CRIS-Team Scopus Importer:2021-12-17

Structural characterization of an ionic liquid in bulk and in nano-confined environment using data from MD simulations - Vučemilović-Alagić, Nataša; Banhatti, Radha D.; Stepic, Robert; Wick, Christian; Berger, Daniel; Gaimann, Mario U.; Baer, Andreas; Harting, Jens; Smith, David M.; Smith, Ana-Suncana (Data in Brief, 2020)
This article contains data on structural characterization of the [C2Mim][NTf2] in bulk and in nano-confined environment obtained using MD simulations. These data supplement those presented in the paper “Insights from Molecular Dynamics Simulations on Structural Organization and Diffusive Dynamics of an Ionic Liquid at Solid and Vacuum Interfaces” [1], where force fields with three different charge methods and three charge scaling factors were used for the analysis of the IL in the bulk, at the interface with the vacuum and the IL film in the contact with a hydroxylated alumina surface. Here, we present details on the construction of the model systems in an extended detailed methods section. Furthermore, for best parametrization, structural and dynamic properties of IL in different environment are studied with certain features presented herein.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Interface-normal number density; Ionic liquid; Molecular dynamics simulations; Nanoconfinement; Radial distributions

Structure and rheology of suspensions of spherical strain-hardening capsules - Aouane, Othmane; Scagliarini, Andrea; Harting, Jens (Journal of Fluid Mechanics, 2021)
We investigate the rheology of strain-hardening spherical capsules, from the dilute to the concentrated regime under a confined shear flow using three-dimensional numerical simulations. We consider the effect of capillary number, volume fraction and membrane inextensibility on the particle deformation and on the effective suspension viscosity and normal stress differences of the suspension. The suspension displays a shear-thinning behaviour that is a characteristic of soft particles such as emulsion droplets, vesicles, strain-softening capsules and red blood cells. We find that the membrane inextensibility plays a significant role on the rheology and can almost suppress the shear-thinning. For concentrated suspensions a non-monotonic dependence of the normal stress differences on the membrane inextensibility is observed, reflecting a similar behaviour in the particle shape. The effective suspension viscosity, instead, grows and eventually saturates, for very large inextensibilities, approaching the solid particle limit. In essence, our results reveal that strain-hardening capsules share rheological features with both soft and solid particles depending on the ratio of the area dilatation to shear elastic modulus. Furthermore, the suspension viscosity exhibits a universal behaviour for the parameter space defined by the capillary number and the membrane inextensibility, when introducing the particle geometrical changes at the steady state in the definition of the volume fraction.
Keywords: Biological Fluid Dynamics: Capsule/cell dynamics; Complex Fluids: Suspensions; Non-Newtonian Flows: Rheology

Structure and rheology of suspensions of spherical strain-hardening capsules - Aouane, Othmane; Scagliarini, Andrea; Harting, Jens (Journal of Fluid Mechanics, 2021)
We investigate the rheology of strain-hardening spherical capsules, from the dilute to the concentrated regime under a confined shear flow using three-dimensional numerical simulations. We consider the effect of capillary number, volume fraction and membrane inextensibility on the particle deformation and on the effective suspension viscosity and normal stress differences of the suspension. The suspension displays a shear-thinning behaviour that is a characteristic of soft particles such as emulsion droplets, vesicles, strain-softening capsules and red blood cells. We find that the membrane inextensibility plays a significant role on the rheology and can almost suppress the shear-thinning. For concentrated suspensions a non-monotonic dependence of the normal stress differences on the membrane inextensibility is observed, reflecting a similar behaviour in the particle shape. The effective suspension viscosity, instead, grows and eventually saturates, for very large inextensibilities, approaching the solid particle limit. In essence, our results reveal that strain-hardening capsules share rheological features with both soft and solid particles depending on the ratio of the area dilatation to shear elastic modulus. Furthermore, the suspension viscosity exhibits a universal behaviour for the parameter space defined by the capillary number and the membrane inextensibility, when introducing the particle geometrical changes at the steady state in the definition of the volume fraction.
CRIS-Team Scopus Importer:2021-02-05
Keywords: capsule/cell dynamics; rheology; suspensions

The interplay of shape and catalyst distribution in the yield of compressible flow microreactors - C Antunes, G.; Jimenez Sanchez, Marco Aurelio; Malgaretti, P.; Bachmann, Julien; Harting, Jens (Journal of Chemical Physics, 2024)
We develop a semi-analytical model for transport in structured catalytic microreactors, where both reactant and product are compressible fluids. Using lubrication and Fick-Jacobs approximations, we reduce the three-dimensional governing equations to an effective one-dimensional set of equations. Our model captures the effect of compressibility, corrugations in the shape of the reactor, and an inhomogeneous catalytic coating of the reactor walls. We show that in the weakly compressible limit (e.g., liquid-phase reactors), the distribution of catalyst does not influence the reactor yield, which we verify experimentally. Beyond this limit, we show that introducing inhomogeneities in the catalytic coating and corrugations to the reactor walls can improve the yield.
CRIS-Team Scopus Importer:2024-10-04

Theoretical framework for two-microswimmer hydrodynamic interactions - Ziegler, Sebastian; Scheel, Thomas; Hubert, Maxime; Harting, Jens; Smith, Ana-Suncana (New Journal of Physics, 2021)
Hydrodynamic interactions are crucial for determining the cooperative behavior of microswimmers at low Reynolds numbers. Here we provide a comprehensive analysis of the scaling laws and the strength of the interactions in the case of a pair of three-sphere swimmers. Both stroke-based and force-based elastic microswimmers are analyzed using an analytic perturbative approach, focusing on passive and active interactions. The former are governed by the cycle-averaged flow field of a single swimmer, which is dipolar at long range. However, at intermediate distances, with a cross-over at the order of 10(2) swimmer lengths, the quadrupolar field dominates which, notably, yields an increase of the swimming velocity compared to individual swimmers, even when the swimmers are one behind another. Furthermore, we find that active rotations resulting from the interplay of the time-resolved swimming stroke and the ambient flow fields and, even more prominently, active translations are model-dependent. A mapping between the stroke-based and force-based swimmers is only possible for the low driving frequency regime where the characteristic time scale is smaller than the viscous one. Finally, we find that the long-term behavior of the swimmers, while sensitive to the initial relative positioning, does not depend on the pusher or puller nature of the swimmer. These results clearly indicate that the behavior of swarms will depend on the swimmer model, which was hitherto not well appreciated.
CRIS-Team WoS Importer:2021-08-13

Thermally induced stress in a nanoconfined gas medium - Rabani, Reza; Heidarinejad, Ghassem; Harting, Jens; Shirani, Ebrahim (Journal of Molecular Modeling, 2020)
Molecular dynamics simulations of static argon gas at three different levels of rarefaction are conducted for a channel of 5.4 nm height to investigate the simultaneous effect of the wall force field and the gas temperature on the stress distribution along the channel height. Using the interactive thermal wall model, different temperatures are applied on the channel walls to be able to investigate the effect of the wall temperature and the induced heat flux through the gas medium on the stress distribution. Considering the monoatomic neutral argon gas, the kinetic, particle-particle virial, and surface-particle virial are considered for computing the stress distribution along the channel height. The normal stress components in the bulk gas region are distributed isotropically regardless of the gas density, temperature, and induced heat flux through the domain, while an anisotropy is observed due to the presence of the surface-particle virial. As the gas becomes hotter, the velocity of the gas atoms increases, and thus the kinetic stress component also increases. Besides, the gas density in the wall force field region reduces which eventually attenuates the surface-particle and particle-particle virial stress within 1 nm from each wall. This effect was also observed as the gas becomes cooler. It is shown that the combination of gas density, wall temperature, and induced heat flux are the main parameters which determine the distribution of stress within the gas medium especially in the wall force field region where repulsive and attractive interactions exist.
CRIS-Team Scopus Importer:2020-06-30
Keywords: Kinetic stress; Rarefaction; Surface virial; Temperature; Wall force field

Transport of neutral and charged nanorods across varying-section channels - Malgaretti, Paolo; Harting, Jens (Soft Matter, 2021)
We study the dynamics of neutral and charged rods embedded in varying-section channels. By means of systematic approximations, we derive the dependence of the local diffusion coefficient on both the geometry and charge of the rods. This microscopic insight allows us to provide predictions for the permeability of varying-section channels to rods with diverse lengths, aspect ratios and charge. Our analysis shows that the dynamics of charged rods is sensitive to the geometry of the channel and that their transport can be controlled by tuning both the shape of the confining walls and the charge of the rod. Interestingly, we find that the channel permeability does not depend monotonically on the charge of the rod. This opens the possibility of a novel mechanism to separate charged rods.
CRIS-Team Scopus Importer:2021-03-19

Two-dimensional Cahn-Hilliard simulations for coarsening kinetics of spinodal decomposition in binary mixtures - Koenig, Bjoern; Ronsin, Olivier J. J.; Harting, Jens (Physical Chemistry Chemical Physics, 2021)
The evolution of the microstructure due to spinodal decomposition in phase separated mixtures has a strong impact on the final material properties. In the late stage of coarsening, the system is characterized by the growth of a single characteristic length scale L similar to Ct(alpha). To understand the structure-property relationship, the knowledge of the coarsening exponent alpha and the coarsening rate constant C is mandatory. Since the existing literature is not entirely consistent, we perform phase field simulations based on the Cahn-Hilliard equation. We restrict ourselves to binary mixtures using a symmetric Flory-Huggins free energy and a constant composition-independent mobility term and show that the coarsening for off-critical mixtures is slower than the expected t(1/3)-growth. Instead, we find alpha to be dependent on the mixture composition and associate this with the observed morphologies. Finally, we propose a model to describe the complete coarsening kinetics including the rate constant C.
CRIS-Team WoS Importer:2021-11-12